Actors and Theaters, Rabbis and Synagogues - Weiss, Zeev (Journal of ancient Judaism, 2017)
The paper discusses the opposition of the rabbis in late antique Palestine to Roman public spectacles and their intentional incorporation of references to the theater, hippodrome, and amphitheater, and their performances, into their sermons. By speaking about these very same issues in their sermons, the rabbis essentially, and perhaps deliberately, became actors in their own communal theater - the synagogue. Based on a careful reading of the literary sources, it is argued that with the ironic use of the same tools and props employed in the theater the rabbis not only sought to condemn public entertainment, including theatrical performances, but also urged their communities to shun this leisure activity in favor of other spectacles more conducive and appropriate to the religious realm.